2012
DOI: 10.1007/s00246-012-0372-y
|View full text |Cite
|
Sign up to set email alerts
|

Transcatheter Closure of Acquired Left Ventricle-to-Right Atrium Shunt: First Case Report in an Infant and Review of the Literature

Abstract: Gerbode defect, a left ventricle to right atrium (LV-RA) communication, is usually congenital. Acquired LV-RA communications are rare and only few case reports of successful trans-catheter closure have been published though none of them were on infants. We hereby report a rare case of LV to RA shunt acquired following surgical repair of Tetralogy of Fallot (TOF). The defect was successfully closed percutaneously with an Amplatzer duct occluder. This is the first reported case of device closure of an acquired G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 5 publications
1
21
0
Order By: Relevance
“…To date, the majority of Gerbode defects have been closed surgically . However, these communications can be closed safely with devices, as shown both in this report, and in previous individual case reports ( and Table ). This is the largest series of catheter closure of acquired LV–RA shunts.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…To date, the majority of Gerbode defects have been closed surgically . However, these communications can be closed safely with devices, as shown both in this report, and in previous individual case reports ( and Table ). This is the largest series of catheter closure of acquired LV–RA shunts.…”
Section: Discussionsupporting
confidence: 66%
“…Surgical correction has been the treatment of choice for true Gerbode defects. There have however, been individual reports of transcatheter closure . We report on the largest series of transcatheter closures of acquired LV‐RA shunts thus far.…”
Section: Introductionmentioning
confidence: 97%
“…The first successful series of patients operated on with a left ventricular to right atrial shunt was reported by Gerbode et al . There are a few case reports of percutaneous closure of acquired Gerbode shunts . There is a small series of four cases of post‐surgical Gerbode defects closed successfully with various devices.…”
Section: Discussionmentioning
confidence: 99%
“…These shunts are traditionally closed surgically with high incidence of complete heart block. There are case reports and small series of mostly acquired and few congenital Gerbode defects closed percutaneously with various types of devices . We report a small series of 12 cases of only congenital Gerbode defects closed with Amplatzer duct occluder II (ADO II) which is specially designed to close long tubular duct in infants.…”
Section: Introductionmentioning
confidence: 99%
“…Surgical correction has been the treatment of choice for true Gerbode defects. There have however, been individual reports of transcatheter closure [2][3][4][5][6][7][8]. We report on the largest series of transcatheter closures of acquired LV-RA shunts thus far.…”
Section: Introductionmentioning
confidence: 99%